2012
DOI: 10.3109/09593985.2012.731675
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effects of Kinesio®Tex taping: A systematic review

Abstract: Kinesio(®) Tex tape (KTT) is used in a variety of clinical settings. The purpose of this study was to investigate the effect of KTT from randomized controlled trials (RCTs) in the management of clinical conditions. A systematic literature search of CINAHL; MEDLINE; OVID; AMED; SCIENCE DIRECT; PEDRO; www.internurse.com; SPORT DISCUS; BRITISH NURSING INDEX; www.kinesiotaping.co.uk; www.kinesiotaping.com; COCHRANE CENTRAL REGISTER OF CLINICAL TRIALS; and PROQUEST was performed up to April 2012. The risk of bias a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
201
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(229 citation statements)
references
References 36 publications
9
201
1
18
Order By: Relevance
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 81%
“…Due to the use of promising KT effects, studies have been developed to investigate the effectiveness of this technique in gait of different populations. In healthy individuals or with musculoskeletal injuries, for example, although isolated studies have demonstrated positive KT results 9,10 , recent systematic reviews do not support the use of this technique on rehabilitation of gait of these populations [11][12][13] . For stroke subjects, studies have also investigated the effects of KT on the gait and also reported promising results 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although studies that tested the effectiveness of NEB on dysfunction in athletes present controversies, recent research has indicated positive effects in the short term period on reducing pain and increasing the ROM of the glenohumeral joint and cervical spine (10)(11)(12)(13)(14) , and improved performance in MTP&RehabJournal 2017, 15: 480 sports that require efforts with repetitive movement and high intensity characteristics (9,(15)(16)(17) . Additionally, the method is described as capable of generating improvement in local circulation, a reduction in edema, facilitation or relaxation of muscles, and improving joint position and proprioception due to optimization of the sensory mechanism (7)(8)18) , characteristics which contribute to improving athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of KT can be explained by gamma motor reflexes of the skin. Adhesion of the kinesiology tape on the skin allows continuous muscle contraction and induces relaxation of muscle tone by inputting information about the level of muscular contraction and allowing repetitive muscle contraction and release [18][19][20]. As shown in Graph 5, there was extremely significant different seen pre and immediate post application of KT in gait speed with p value of 0.0187.…”
Section: Discussionmentioning
confidence: 77%